Giardiasis in infancy diarrhoea. Issue 9 (September 1980) - Monaghan, H; Garvey, R G; Egan-Mitchell, B; Noone, P; Flynn, J; McNicholl, B
Abstract : Of 435 infants with diarrhoea aged under one year, 6% were found to have Giardia lamblia; the incidence ranged from 3% housed infants to 12% in itinerant infants. All infants had duodenal fluid and faeces examined. Infants under 12 weeks may experience severe diarrhoea in association with infection by this parasite, but seem more likely to respond to metronidazole than older infants.